Language and identity in modern Egypt - Bassiouney, Reem, 1973- (Edinburgh University Press, 2014)
How is language used in Egyptian public discourse to illuminate the collective identity of Egyptians? How does this identity relate to language form and content? Reem Bassiouney explores these questions by drawing on sources including newspaper articles, caricatures, blogs, patriotic songs, films, school textbooks, TV talk-shows, poetry and novels As well as furthering our understanding of the relationship between identity and language, this book yields insights about the intricate ways in which media and public discourse help shape and outline identity through linguistic processes. Key Features Offers an in-depth study of identity in modern Egyptian public discourse Focuses on nationalist discourse before, during and after the Egyptian revolution of 2011 Based on a broad, and representative selection of data Helps us to decode and understand the messages put forward by the competing factions in Egyptian politics